A feasibility study on airflow vented ridge roll - Aureada, Crisencia C. (College of Engineering, 1997)
The Airflow Vented Ridge Roll (AVRR) is an innovative accessory made of plain GI sheet, designed to facilitate air circulation in the house. It is a unique attachment on the roof that releases the trapped hot air making the immediate surrounding, that is the home, cooler. The AVRR will be introduced to the market for the first time. This poses a lot of questions that this paper aims to address. Will the product be accepted in the market? is the project manufacturable within the local setting? will the project be profitable? what kind of business establishment will be best for this business venture? Will the nation at large benefit from this project? The time-frame for the project is five years. The first question was addressed by the market study. A target market share of 469,980 pieces of AVRR was computed for the next five years. The target market set as 5% of the market share for the next five years. The second question was further investigated with the technical study. A plant was set-up at Block 5 Lot 53 Governor Drive General Trias, Cavite. The production schedule for one year was also drawn- there will be two 8-hour shifts with 4 hours overtime. The profitability of the project was seen in the financial study. An initial investment of Php 31.59M is needed for a net income after ta of PhP 1,629,691.55 for the first year, PhP 1,978,893.88 for the second year, PhP 2,329,708.95 for the third year, PhP 2,679,886.35 for the fourth year, and PhP 3,596,873.13 for the fifth year. It will take approximately 27 months to recover the total project investment. An IRR of 19.275% was computed making the project more attractive than the set MARR of 15% The social impacts are the following: Generation of jobs for 24 employees, payment of taxes to the Philippine Government, pollution-free production, addition of industry. The enterprise is projected to be profitable for the next five operating years.The facilities and manpower is adequate. The project is very feasible because the benefits outweighs the costs.